Electric field interactions between closely abutting excitable cells. - Sperelakis, N.
This review article summarizes some of the electrophysical evidence and morphological evidence against the hypothesis that the myocytes of cardiac muscles and visceral smooth muscles are profusely interconnected by low-resistance pathways (e.g., tunnels or gap-junction channels), which would give rise to a long length constant. Instead, propagation of the action potential (AP) is discontinuous, with a substantial junctional delay time at the cell junctions. Since the entire surface membrane of each cell becomes excited nearly simultaneously, a plot of propagation time versus distance (along a strand of cells) exhibits a typical staircase shape. This article demonstrates that the electric field that develops in the narrow junctional cleft (negative cleft potential) when the prejunctional membrane (pre-JM) fires an AP acts to depolarize the post-JM to its threshold. This mechanism, by itself, can account for transmission of excitation from cell to cell, but accessory mechanisms that act additively include K+ accumulation in the junctional clefts, gap-junction channels, and capacitive coupling
Keywords: Action potential; Capacitive coupling; Cardiac muscles; Closely abutting excitable cells; Cultured heart cell monolayers; Discontinuous staircase propagation; Electric field interactions; Electrophysical evidence; Ephaptic transmission; Gap-junction channels; Low-resistance pathways; Morphological evidence; Myocardial cells; Myocytes; Negative cleft potential; Prejunctional membrane; Tunnels